2017
DOI: 10.12657/denbio.077.010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and structure of mountain autochthonous spruce-beech forests: impact of hilltop phenomenon, air pollutants and climate

Abstract: Mountain forests are strongly influenced by the extreme climate, short growing season and stress from environmental pollution and lower fertility of soils. The paper analyses the effect of the environment (climate and air pollutants) on the structure, production and dynamics of autochthonous spruce-beech forest stands in protected areas in the summit parts of the Orlické hory Mts., Czech Republic. The spatial pattern of tree layer was random in lower parts below the summit and aggregated under the hilltop phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 65 publications
12
41
0
Order By: Relevance
“…(3) Increasing CO 2 content can increase the biomass (and wood production) of beech stands in newly occupied areas at higher altitudes (Machar et al 2017b). Králíček et al (2017) confirmed these results by founding of strong correlation between the radial increment of European beech and the temperature in mountain areas. Long-term simulations of climate change's impact on forest dynamics in Silver fir-European beech stands in Dinaric Mountains in Slovenia (Mina et al 2017) revealed that European beech will be favoured by higher temperatures in contrast to drought-induced growth reduction in Silver fir.…”
Section: Discussionsupporting
confidence: 68%
“…(3) Increasing CO 2 content can increase the biomass (and wood production) of beech stands in newly occupied areas at higher altitudes (Machar et al 2017b). Králíček et al (2017) confirmed these results by founding of strong correlation between the radial increment of European beech and the temperature in mountain areas. Long-term simulations of climate change's impact on forest dynamics in Silver fir-European beech stands in Dinaric Mountains in Slovenia (Mina et al 2017) revealed that European beech will be favoured by higher temperatures in contrast to drought-induced growth reduction in Silver fir.…”
Section: Discussionsupporting
confidence: 68%
“…(Bulušek et al 2016;Králíček et al 2017). On the other hand, in those studies a positive relationship of recruits and tree layer in beech was confirmed on plots with extreme site conditions due to natural layering.…”
Section: Discussionmentioning
confidence: 82%
“…Similar numbers like those were reported by others researches in the Czech Republic from spruce-beech near-natural forest in the Orlické hory Mts. -37,230 recruits ha -1 Králíček et al 2017), while higher regeneration density were observed in the Voděrady Beechwoods -60,859 recruits ha -1 , in Krkonoše Mts. -75,395 recruits ha -1 (Vacek et al 2015a) or in old-growth forest in Slovenia -62,000 recruits ha -1 (Dusan et al 2007).…”
Section: Discussionmentioning
confidence: 88%
“…Natural and semi-natural mixed forests are currently very intensively studied subject (Paluch 2007;Kucbel 2010;Liira et al 2011;Králíček et al 2017;Meier et al 2017). In comparison with managed stands, these forests have many-times higher species diversity (Lindenmayer & Franklin 2002;Bauhus et al 2009), self-regulatory ability (Korpeľ 1995) and stability against external influences (Knoke et al 2008;Liira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Very diverse structure of fenced forest stand was also observed from other research in the Trčkov NNR (B; index 8.61) compared to lower complex diversity in unfenced stand (B;7.66;Vacek et al 2013), such as in other mixed not fenced spruce-beech forest in Orlické hory Mts. (B 6.57 -8.05;Králíček et al 2017). Study forest stands with pronounced age, spatial and species differentiation are generally considered as ecologically stable (Klopcic & Boncina 2011).…”
mentioning
confidence: 99%